Nanotechnological Applications in Current Innovative Approaches in Dairy Technology- A review - Binnur Kaptan (Journal of Agricultural Sciences)
Nanotechnology offers significant potential in the dairy industry, influencing a range of products such as milk, cheese, yogurt, butter, fermented milk, and buttermilk. The use of both bottom-up and top-down processing approaches yields extensive insights into the intrinsic and extrinsic characteristics of dairy products. A variety of nano-techniques including nanoemulsion, nanoencapsulation, nanoliposomes, nanotubes, nanofibers, and nanocapsules are employed within the dairy industry. These methods, in conjunction with nanosensors, nanolaminates, and nanocoatings, act as efficient packaging solutions, providing critical information on product safety, stability, and quality. Nanotechnology is also highly effective in detecting foodborne pathogens and excels in pathogen control. It plays an essential role in food fortification by encapsulating nutrients, ingredients, and compounds, thus enhancing the texture, taste, aroma, quality, and nutritional value of food. Notably, nanoparticles such as zinc oxide, silver, and titanium demonstrate potent mechanisms for disrupting bacterial cell walls, aiding in compound absorption, and improving physiological functions. This review presents the applications of nanotechnology in the dairy industry, along with pertinent studies and their outcomes regarding the utilization of these technologies in dairy products.